1996
DOI: 10.1007/bf00115637
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and stomach cancer

Abstract: Epidemiologic evidence on the relation between nutrition and stomach cancer is reviewed. Stomach cancer shows a distinct international variation and dramatic worldwide decline. These descriptive features suggest that dietary factors are important in determining the risk of stomach cancer. The authors assessed relevant data regarding specific dietary hypotheses in the etiology of stomach cancer. A negative association with fresh vegetables and fruits is highly consistent in numerous case-control studies in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
3
13

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(143 citation statements)
references
References 83 publications
6
121
3
13
Order By: Relevance
“…26 Helicobacter pylori infection, salt intake and smoking and dietary mutagens such as nitrosamines intake were known factors of developing pre-cancerous lesions and well-differentiated type of gastric adenocarcinoma. 1,2,29,30 In our study, the frequency of the CYP2A6 homozygote deletion was higher among well-differentiated adenocarcinoma cases and this increase admitted statistical significance (OR ϭ 4.91, 95% CI 1.17-20.52). The result considered that the CYP2A6 homozygote deletion genotype was one of the risk factors of developing well-differentiated type of gastric adenocarcinoma.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…26 Helicobacter pylori infection, salt intake and smoking and dietary mutagens such as nitrosamines intake were known factors of developing pre-cancerous lesions and well-differentiated type of gastric adenocarcinoma. 1,2,29,30 In our study, the frequency of the CYP2A6 homozygote deletion was higher among well-differentiated adenocarcinoma cases and this increase admitted statistical significance (OR ϭ 4.91, 95% CI 1.17-20.52). The result considered that the CYP2A6 homozygote deletion genotype was one of the risk factors of developing well-differentiated type of gastric adenocarcinoma.…”
Section: Discussionsupporting
confidence: 53%
“…Epidemiological and experimental evidence have indicated that excess salt intake, which promotes cell replication, increases gastric cancer risk. 1,2 There is considerable evidence to support the view that carcinogenic N-nitrosamine derivatives are important factors in human cancer, including gastric cancer. The chemical mechanisms of carcinogenesis by these nitrosamines in humans are therefore of considerable interest.…”
mentioning
confidence: 99%
“…The relative risks reported ranged from 1.5 to 6.7 for various measures of salt intake [14]. In several other case-control studies no association was reported for (total) salt or sodium intake [43][44][45], salted foods [11,13,43,46], for use of table salt [10,47] or salt added to food [8,13,15,16,47], preference of foods with a salty taste [8,12,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiological studies have investigated the association between stomach cancer risk and salt or sodium intake (e.g., [2][3][4]), salted foods (e.g., [5][6][7]), salt added during cooking or at table (e.g., [8][9][10]) and preference of salty taste (e.g., [11][12][13]). In many case-control studies a positive association was reported between an indicator of high salt intake and stomach cancer risk, but in nearly all cohort studies no association was observed [14].…”
Section: Introductionmentioning
confidence: 99%
“…There is a distinct familial risk for gastric cancer, and studies have demonstrated that the risk is higher for siblings than for parents and offspring 4. A high salt intake has been identified as a risk factor for gastric cancer in case‐control studies 5. Red and processed meat intake was associated with a 43% increase in the risk for gastric cancer 6.…”
Section: Risk Factors For Gastric/gej Cancersmentioning
confidence: 99%